2020
DOI: 10.1021/jacs.0c02534
|View full text |Cite
|
Sign up to set email alerts
|

On-Surface Synthesis of a π-Extended Diaza[8]circulene

Abstract: Experimental procedures, compound characterization, spectra, details of DFT calculations, CO-STM images, and dI/dV simulations (PDF) X-ray crystallographic data for 7b (CIF) X-ray crystallographic data for 8b (CIF) X-ray crystallographic data for 9b (CIF) X-ray crystallographic data for 10b (CIF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 71 publications
(39 reference statements)
2
53
1
Order By: Relevance
“…In contrast to wet chemistry, the on‐surface reaction is free from the solubility issue and thus becomes of central importance to synthesize large polycyclic aromatic hydrocarbons (PAHs) such as graphene nanoribbons [29–31] . Furthermore, a large adsorption energy to the metal substrate induces planarization, leading to syntheses of unique PAHs, which are hardly obtained in solution [32] …”
Section: Figurementioning
confidence: 99%
“…In contrast to wet chemistry, the on‐surface reaction is free from the solubility issue and thus becomes of central importance to synthesize large polycyclic aromatic hydrocarbons (PAHs) such as graphene nanoribbons [29–31] . Furthermore, a large adsorption energy to the metal substrate induces planarization, leading to syntheses of unique PAHs, which are hardly obtained in solution [32] …”
Section: Figurementioning
confidence: 99%
“…[29][30][31] Furthermore, a large adsorption energy to the metal substrate induces planarization, leading to syntheses of unique PAHs, which are hardly obtained in solution. [32] Here, we employed newly synthesized 11,11,12,12-tetraphenyl-1,4,5,8-tetraazaanthraquinodimethane 1 as well as three other derivatives as precursors. [33] The structures were directly identified with bond-resolved STM at 4.3 K. We found CÀN bond formations between pyrazine and phenyl groups after annealing at 370 K on Au(111).…”
mentioning
confidence: 99%
“…The demonstrated nanoarchitectonics strategy would be applied to the other units to produce various carbon nanostructures. Nakamura et al reported the synthesis of π-extended diaza [8]circulene through a combination of in-solution and on-surface syntheses (Figure 9) [79]. The final form of π-extended diaza [8]circulene possessing six hexagons and two pentagons cannot be obtained only with solution-based reaction processes.…”
Section: Atom/molecular-level Nanoarchitectonics Synthesismentioning
confidence: 99%